2014
DOI: 10.14309/crj.2014.13
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous Small Cell Neuroendocrine Carcinoma and Adenocarcinoma of the Colon: A Link for Common Stem Cell Origin?

Abstract: Synchronous carcinomas have been recognized for over a century, with synchronous primary adenocarcinoma of the colon reported to range from 2–11% of cases involving this type of malignancy. Small cell carcinomas occur frequently with colorectal adenomas; however, despite these reports and a known adenoma-to-carcinoma sequence, scarce literature exists on synchronous colorectal adenocarcinoma and small cell carcinomas. We present a rare cancer of synchronous small cell neuroendocrine carcinomas and discuss a po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Few authors suggest common link between the pathogenesis of the colorectal NET and adenocarcinoma [ 8 , 9 ]. Kato et al [ 9 ] reported a CK20 positive (a common marker found in colorectal adenocarcinoma) large cell NET that occurred synchronously to a colorectal adenocarcinoma, suggesting the theory that different types of GI neoplasm might originate from a common stem cell clone which might share a similar genetic mutation(s) during early oncogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Few authors suggest common link between the pathogenesis of the colorectal NET and adenocarcinoma [ 8 , 9 ]. Kato et al [ 9 ] reported a CK20 positive (a common marker found in colorectal adenocarcinoma) large cell NET that occurred synchronously to a colorectal adenocarcinoma, suggesting the theory that different types of GI neoplasm might originate from a common stem cell clone which might share a similar genetic mutation(s) during early oncogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 100 reports have been published on SCC [ 2 ]. Its incidence comprises 0.1% of colorectal cancers [ 3 , 4 ]. In cases of inflammatory bowel disease, the standardized incidence ratio of SCC is 1.7 [ 5 ].…”
Section: Introductionmentioning
confidence: 99%